European Universities Best Practices: The Case of INVEST EU Alliance - Kokkinos, Konstantinos; Samaras, Nicholas; Iatrellis, Omiros (European Scientific Journal, ESJ, 2024)
Established in 2018, the European Universities Initiative (EUI) strives to foster collaboration and integration among higher education institutions across Europe. The EUI’s core objectives encompass forging transnational alliances, facilitating mobility, championing multidisciplinary approaches, celebrating linguistic diversity, advancing innovation and research, prioritizing student-centered learning, and nurturing long-term sustainability. Central to this initiative is the enhancement of education quality and the promotion of student-centric learning methodologies. Within the scope of the EUI, the INVEST European University stands out as one of the 47 integrated alliances, endorsed by the European Commission. INVEST is dedicated to crafting distinctive collaborative educational paradigms that contribute significantly to regional progress and sustainability. This paper provides a comprehensive overview of the INVEST Joint Education Model, showcasing a range of excellent practices that position the alliance as a key player in the European educational landscape. Specifically, this paper delves into the strategic quality assurance framework, the unified pedagogical approach supporting diverse educational products, the dynamic collaborative platforms like living labs that engage stakeholders and serve as experimentation grounds, the enriching fellowship programs, faculty and student mobility initiatives, eco-friendly digitalization of services, and innovative entrepreneurship and internationalization processes. This study not only offers insightful recommendations but also tangible real-world examples for instructional and support staff navigating the realm of digital transformation within inter-institutional partnerships.